The development of low-cost Cloud-Based CO2 Monitoring System for green city application / Mohamad Hanif Md Saad ... [et al.] - Md Saad, Mohamad Hanif; Sarnon, Mohd Zaki; Hussain, Aini; Rosli, Mohd Rezdwan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Nowadays, our society, especially those big city dwellers, are very concerned about the air quality they breathe in since the quality of air has a great impact on their health and will affect how they live. As such, availability of an affordable carbon dioxide (CO2) Monitoring System that can provide a standalone real-time CO2 monitoring is very much needed. Such a system could serve as a useful tool for the local council to identify the level of concentration of harmful gases in selected locations. This study presents the results of a qualitative study undertaken for a period of six days. It also discussed the design, development and implementation of the CO2 monitoring system. The findings suggest that the level of CO2 concentration varies throughout the day and affects the environment in a green city. Quantitative data were made available via this low-cost web cloud-based monitoring response to sensing taken in 1-minute intervals, continuously. Thus, it can be concluded that the developed low-cost cloud-based air quality (CO2) monitoring system with a real-time graphical display was successfully implemented and provided information on how the environments are affected from people’s daily activities.